DETECTION TOOL FOR BORAX CONTENT IN MEATBALL FOOD - Gusrina Rahayu; Nadia Khumaeroh; Fatiatun Fatiatun; Kusnanto Mukti Wibowo (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2024)
The use of prohibited food additives is still often found and is even increasing, especially among food entrepreneurs. Small industries or households generally produce these additives. One type of food preservation that is currently widely used is borax and formalin. This research aims to determine the tool's characteristics for detecting preservatives (borax) in food and the presence/absence of preservatives (borax) in meatball food. The method used in this research is an experiment using Arduino, TCS320 colour sensor, LCD, and mini projectboard. The results obtained in this research can conclude that borax is still used in meatball-type food. However, whether the seller uses borax on purpose or the flour used contains borax without the seller knowing it has yet to be known. The borax content itself dramatically influences the frequency value. Based on the results of checks using tools that have been made, meatballs in Wonosobo that are sold to the public have been detected to contain 15% borax. This amount shows a high value and is dangerous for the health of those who consume this food. This research is significant for people who consume meatballs.